2022
DOI: 10.1044/2022_jslhr-21-00651
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Daily Hours of Sound Therapy on Tinnitus Relief for People With Chronic Tinnitus: A Randomized Controlled Study

Abstract: Purpose: Tinnitus is defined as the perception of sounds in the absence of extrinsic sound stimuli. Sound therapy is an option for tinnitus rehabilitation, which aims to mitigate the functional and emotional effects of tinnitus. Several studies have reported that a longer duration of sound therapy may result in a greater tinnitus relief effect. However, the relationship between the daily hours of sound therapy and the tinnitus relief effect remains unclear. Thus, we aimed to evaluate the tinnitus r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
2
4
0
1
Order By: Relevance
“…Those that used the sound therapy more hours per day experienced more benefit. This relationship has been observed before (Jin et al, 2022). Hence, the non-compliant participants in our study likely pulled the average down.…”
Section: Discussionsupporting
confidence: 71%
“…Those that used the sound therapy more hours per day experienced more benefit. This relationship has been observed before (Jin et al, 2022). Hence, the non-compliant participants in our study likely pulled the average down.…”
Section: Discussionsupporting
confidence: 71%
“…Future studies should extend the trial duration beyond 12 months to better understand the long-term effects. Second, the daily treatment time for patients was relatively short; a longer daily sound therapy duration might enhance the potential for improving tinnitus relief 9 . There is evidence that continuous sound therapy for longer periods, such as 3 h per day for > 6 months, could yield better results 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Sound therapy, assessed through subjective evaluations, has demonstrated effectiveness in tinnitus management. The efficacy of sound therapy improves with the duration of daily treatment; it can be effective as a standalone method without additional counseling 8 , 9 . Vernon 10 demonstrated that tinnitus masking, a standard monotone therapy, involves using external noise to distract the patient's attention and reduce the contrast between the tinnitus signal and background activity within the auditory system.…”
Section: Introductionmentioning
confidence: 99%
“…Sound therapy is a typical rehabilitation approach for patients with chronic tinnitus, aiming to habituate patients to tinnitus and reduce focus on it [7][8][9]. In a study by Jin et al (2022), 14 of 38 participants with chronic tinnitus who received sound therapy for at least 3 h daily for 3 months reported significant tinnitus relief [9]. In another study, 5 of 15 participants with chronic tinnitus who received sound therapy reported significant relief from tinnitus [8].…”
Section: Introductionmentioning
confidence: 99%
“…Whether rehabilitation combining sound and electrical stimulation is more effective than traditional sound therapy remains unclear. Studies on sound therapy alone have also reported significant tinnitus relief in 30-50% of participants when assessing individualized tinnitus relief [9,11]. However, studies on sound therapy alone and those combining sound and electrical stimulation are not directly comparable because of differences in participant characteristics, rehabilitation duration, and assessment methods.…”
Section: Introductionmentioning
confidence: 99%